Notable differences in gene expression between injured turbot (Scophthalmus maximus) and brill (Scophthalmus rhombus) skin - Estêvão, João Luis Correia (2017)
Dissertação de mestrado, Engenharia Biológica, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015